Ground Covers, Rock Garden Plants and Ornamental Grasses - van der Hoeven, Gustaaf A. (My University, 1978)
This publication assists homeowners with landscape planning. This information can be used to select plant materials for particular locations.
C468_1978_04
Keywords: C468; Lawn and Garden; C